If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6a + -3(a + 2) = 0 Reorder the terms: 6a + -3(2 + a) = 0 6a + (2 * -3 + a * -3) = 0 6a + (-6 + -3a) = 0 Reorder the terms: -6 + 6a + -3a = 0 Combine like terms: 6a + -3a = 3a -6 + 3a = 0 Solving -6 + 3a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3a = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 3a = 0 + 6 3a = 0 + 6 Combine like terms: 0 + 6 = 6 3a = 6 Divide each side by '3'. a = 2 Simplifying a = 2
| 1x-10+x-5x+1=14+3x-8-1 | | 4xy-5y+2=0 | | -2x=3(x-5)+6 | | 3x-10=-4x+22 | | 3p(p-1)=18 | | 7x=50-1 | | 3(-8)+[6(-2)]= | | 3n^3-4n^2+n=0 | | 3(-8)+[16(-2)]= | | -5(4x+5)=4+2(4x-8) | | n^2+2n+24=0 | | 3(2z+7)+4=5(z-3) | | 1=3x-21 | | (y^2+2y)+(3y^2+4y+2)=0 | | 7(x+1)=6-2(7x+7) | | x^2=6x+10 | | 3X+3=2X+2 | | 9+6x+4-x=16+7-5 | | k=LMN | | 50x+20(x+6)+10(x+6)+5*2*(x+6)=1140 | | 13-4=-6x+17 | | 4x^3+x^2-36x-9=0 | | 6(-3x+1)=-10(x+1)+16-8x | | 2x^2+4x+20=0 | | 9x+8-10x+2=8x-9x-3 | | 5x+1=1+5x | | (n-2)+(n-1)+5n=47 | | 3x+10=3x+8 | | 7x=8x^2 | | 15(c+3)+6=61 | | x^4-2x^3+x^2-8x-12=0 | | 7(3x-5)+3(16-4x)=4(2x+5)-11 |